Allamah Ṭabaṭabai’s View on Nafs Al-Amr: An Ontological Basis for the Correspondence of Proposition - Sihabudin Sihabudin (Ulumuna, 2016)
One of the most prevalent critics of correspondence theory of truth is the scope it contains. The objection is that the proponents of this theory could solely apply their theory of truth to some limited domain−which has something to correspond to− like science, but they would fail for other domain− which has no something to correspond to− like morality. In this study, I aim to defend the theory of correspondence by considering the concept of nafs al-amr advanced by ‘Allāmah Ṭabāṭabā’ī as a basis to which every proposition reaches its correspondence. As a realist, ‘Allāmah Ṭabāṭabā’ī whose view holds the fundamentality of existence, excludes everything other than existence. Hence, in his epistemology every proposition would correspond to reality if and only if it refers to the existence. He notices that human concepts which will eventually form a proposition unveil some different parts of reality. They occasionally indicate something external, like table, something internal, like logical concepts, even something non-existential, like nothingness. The concept of nafs al-amr as subsistence in general includes the subsistence of every concept and serves as an ontological basis to which a proposition gets its correspondence. DOI: http://dx.doi.org/10.20414/ujis.v20i1.795